Tingkat Fertilisasi dan Perkembangan Embrio Mencit yang Diberi Ekstrak Buah Merah - S Said; O P Astirin; S Wahyuningsih (Faculty of Animal Science, Bogor Agricultural University, 2011)
In the present study examined the influence of red fruit extract (RFE) on fertilization rate and development of mice embryos during the pre-implantation stage. The application of RFE dose 0 ml/head/day, 0.05 ml/head/day, and 0.1 ml/head/day for seven days were conducted to examine its influence at the level of fertilization, then the application of RFE was continued during 0-3 days stage of pregnancy (0 day of pregnancy is the formation of the vaginal plug). The super-ovulation of the white mice was done by injecting of 5 IU PMSG and hCG (48 hours after PMSG), folowed by mating the females with males with ratio 1:1. The single-cell-embryos were collected 20 hours after the injection of hCG. The eggs were then fixed and stained before examinating the normal fertilization of eggs (formation 2 pronucleus). The morula and blastocysts were collected 84 hours after injection of hCG. The influence of the RFE with dose 0.1 ml on normal fertilization rate (formation 2 PN), significantly higher (46.01%) compared with dose 0.05 ml (37.51%) and controlled (16.38%). However, the influence of RFE with dose of 0.05 ml and 0.1 ml on the growth of pre-implantation stage embryos may inhibit the growth of mice embryos during the pre-implantation stage in vivo.